The Effect of Performance Benefits, Workload, Work Environment, and Organizational Culture on Work Motivation of Employees Office Office of Class I Airport Organizing Unit in Papua - Mohammad Taufiq Rahman; Zakaria Zakaria; Agus Sudarya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the effect of Performance Allowance, Workload, Work Environment, and Organizational Culture on Employee Motivation at the Class I Airport Organizing Unit Office in Papua. This research was conducted at the Mopah Merauke Class I Airport Management Unit Office, Wamena Class I Airport Management Unit Office, and Domine Eduard Osok Sorong Class I Airport Operator Unit with a population of 231 employees. To get an objective research sample, the researchers used the Slovin so that 146 respondents were obtained. The independent variables in this study are Performance Allowance, Workload, Work Environment, and Organizational Culture. The results of the analysis show that the variables of Performance Allowance, Workload, Work Environment, and Organizational Culture have a positive and significant effect on employee motivation. The variable of employee work motivation is influenced by the variables of Performance Allowance, Workload, Work Environment and Organizational Culture by 50.6%, while the remaining 49.4% is influenced by other factors outside of this study.